Suitability of a liquid larval diet for rearing the Philippines fruit fly Bactrocera philippinensis (Diptera: Tephritidae). (19th August 2014) - Resilva, Sotero S.; Obra, Glenda B.; Chang, Chiou Ling
Abstract : In this study, a liquid larval diet as an artificial rearing medium was successfully tested for the Philippines fruit fly Bactrocera philippinensis Drew & Hancock. The biological parameters studied were pupal weight, adult emergence and fliers, sex ratio, fecundity and fertility. The insects performed most satisfactorily if corn (maize) oil was added to the liquid medium. Compared with the standard sponge 'Kalle' cloth, three locally available absorbent materials showed promise as a support matrix for feeding larvae.